Fabricating 43-μm-Thick and 12% Efficient Heterojunction Silicon Solar Cells by Using Kerfless Si(111) Substrates. (1st January 2015) - Du, Chen-Hsun; Chen, Chien-Hsun; Wang, Teng-Yu; Hsiao, Jui-Chung; Yeh, Chun-Ming; Chen, Chun-Heng; Yeh, J. Andrew; Yu, Peichen
Abstract : A 43-μm-thick Si(111) substrate was obtained using the stress-induced lift-off method with a screen-printed metal paste layer as the stress-generation layer. The reflection of the metal-removed side of the Si(111) substrate was lower than that of the exfoliated side because of high surface roughness resulting from the reaction between the metal paste and the silicon substrate at 700°C. After aggressive etching with an alkaline solution for the peeled silicon substrate, the efficiency of the heterojunction silicon solar cell was improved from 0.87% to 12%.